NGTS-1b: a hot Jupiter transiting an M-dwarf. Issue 4 (3rd November 2017) - Bayliss, Daniel; Gillen, Edward; Eigmüller, Philipp; McCormac, James; Alexander, Richard D; Armstrong, David J; Booth, Rachel S; Bouchy, François; Burleigh, Matthew R; Cabrera, Juan; Casewell, Sarah L; Chaushev, Alexander; et al.
Abstract: We present the discovery of NGTS-1b, a hot Jupiter transiting an early M-dwarf host ( T eff, * = $3916\, ^{+71}_{-63}$  K) in a P  = 2.647 d orbit discovered as part of the Next Generation Transit Survey (NGTS). The planet has a mass of $0.812\, ^{+0.066}_{-0.075}$   M J,  making it the most massive planet ever discovered transiting an M-dwarf. The radius of the planet is $1.33\, ^{+0.61}_{-0.33}$   R J . Since the transit is grazing, we determine this radius by modelling the data and placing a prior on the density from the population of known gas giant planets. NGTS-1b is the third transiting giant planet found around an M-dwarf, reinforcing the notion that close-in gas giants can form and migrate similar to the known population of hot Jupiters around solar-type stars. The host star shows no signs of activity, and the kinematics hint at the star being from the thick disc population. With a deep (2.5 per cent) transit around a K  = 11.9 host, NGTS-1b will be a strong candidate to probe giant planet composition around M-dwarfs via James Webb Space Telescope transmission spectroscopy.